Recent advances in MXene-based materials for high-performance metal-air batteries - Ababay Ketema Worku; Molla Asmare Alemu; Delele Worku Ayele; Muluken Zegeye Getie; Minbale Admas Teshager (Green Chemistry Letters and Reviews)
MXene is a novel type of 2D sheet nanomaterial that shows great application potentials in a variety of fields due to its advantages, such as high electrical conductivities, high surface areas, superior mechanical strength, functional transition metal surfaces, tunable surface chemistries, and excellent dispersion in various solvents. Additionally, due to its adaptability for a diverse range of applications, such as electrochemical energy storage devices, electrocatalysis, sensors, biomedical applications, membranes, flexible and wearable devices, etc., MXene is emerging as a "rising star" material. The scientific community will benefit from having a summary of the most recent research on this family of materials as these applications encourage greater interest in MXene research. In this review, we began by thoroughly summarizing the structures, characteristics, and production methods of materials based on MXenes. Then, a summary of MXenes-based materials' uses for metal air batteries has also been provided. Additionally, in order to inform the readers on the current state of MXenes' growth, we also shared our thoughts and explored their future directions. This review's data should make it easier to translate lab-scale discoveries into products that are marketable.